Prosthetic joint infection diagnosis using broad-range PCR of biofilms dislodged from knee and hip arthroplasty surfaces using sonication - Gomez, Eric; Cazanave, Charles; Cunningham, Scott A; Greenwood-Quaintance, Kerryl E; Steckelberg, James M; Uhl, James R; Hanssen, Arlen D; Karau, Melissa J; Schmidt, Suzannah M; Osmon, Douglas R; Berbari, Elie F; Mandrekar, Jayawant; et al. (Journal of clinical microbiology, 2012)
Periprosthetic tissue and/or synovial fluid PCR has been previously studied for prosthetic joint infection (PJI) diagnosis; however, few studies have assessed the utility of PCR on biofilms dislodged from the surface of explanted arthroplasties using vortexing and sonication (i.e., sonicate fluid PCR). We compared sonicate fluid 16S rRNA gene real-time PCR and sequencing to culture of synovial fluid, tissue, and sonicate fluid for the microbiologic diagnosis of PJI. PCR sequences generating mixed chromatograms were decatenated using RipSeq Mixed. We studied sonicate fluids from 135 and 231 subjects with PJI and aseptic failure, respectively. Synovial fluid, tissue, and sonicate fluid culture and sonicate fluid PCR had similar sensitivities (64.7, 70.4, 72.6, and 70.4%, respectively; P > 0.05) and specificities (96.9, 98.7, 98.3, and 97.8%, respectively; P > 0.05). Combining sonicate fluid culture and PCR, the sensitivity was higher (78.5%, P < 0.05) than those of individual tests, with similar specificity (97.0%). Thirteen subjects had positive sonicate fluid culture but negative PCR, and 11 had negative sonicate fluid culture but positive PCR (among which 7 had prior use of antimicrobials). Broad-range PCR and culture of sonicate fluid have equivalent performance for PJI diagnosis.